IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON BRAND LOYALTY: MEDIATING EFFECT OF BRAND ATTITUDE IN BANKING SECTOR - Faisal, Muhammad (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study investigates the effects of two dimensions of Corporate Social Responsibility (CSR) i.e., ethical and economic on Brand Loyalty (BL) in banking industry of Pakistan. The author tested how the brand attitude work as a mediator between the two dimensions of CSR (ethical and economic) and Brand Loyalty. This research provides valuable insight into the complex dynamics of brand loyalty through Corporate Social Responsibility, which has significant implications for banking industry. The result confirms that brand attitude mediates the relationship of CSR and Brand Loyalty. The study's conclusions are helpful to assists the banking industry to develop effective marketing strategy and take decision regarding the investment in corporate social responsibility relevant factors to create brand loyalty, which will ultimately result in a competitive edge. This study is unique kind of study to conduct with respect to prescribed hypothesized model/framework. Many studies have discussed the issue of CSR, but very few are found in the Pakistan, particularly in the banking sector.  The author includes the brand attitude between the CSR dimensions (ethical and economic) and Brand loyalty as a mediator.